2004
DOI: 10.1128/jvi.78.23.13153-13162.2004
|View full text |Cite
|
Sign up to set email alerts
|

SYNCRIP, a Member of the Heterogeneous Nuclear Ribonucleoprotein Family, Is Involved in Mouse Hepatitis Virus RNA Synthesis

Abstract: Several cellular proteins, including several heterogeneous nuclear ribonucleoproteins (hnRNPs), have been shown to function as regulatory factors for mouse hepatitis virus (MHV) RNA synthesis as a result of their binding to the 5 and 3 untranslated regions (UTRs) of the viral RNA. Here, we identified another cellular protein, p70, which has been shown by UV cross-linking to bind both the positive-and negative-strand UTRs of MHV RNA specifically. We purified p70 with a a one-step RNA affinity purification proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Members of the hnRNP family (hnRNP A1 and PTB) were shown to bind to 5 0 UTR and 3 0 UTR and were suggested to mediate a cross talk between 5 0and 3 0 -terminal genome regions Lai, 1999, 2001). Furthermore, it was reported that interactions of hnRNP A1 and PTB modulate viral RNA synthesis and SYNCRIP silencing leads to reduced virus production (Choi et al, 2004). Similar observations were made for TGEV.…”
Section: Possible Roles Of Cellular Proteins In Coronavirus Replicationsupporting
confidence: 64%
See 1 more Smart Citation
“…Members of the hnRNP family (hnRNP A1 and PTB) were shown to bind to 5 0 UTR and 3 0 UTR and were suggested to mediate a cross talk between 5 0and 3 0 -terminal genome regions Lai, 1999, 2001). Furthermore, it was reported that interactions of hnRNP A1 and PTB modulate viral RNA synthesis and SYNCRIP silencing leads to reduced virus production (Choi et al, 2004). Similar observations were made for TGEV.…”
Section: Possible Roles Of Cellular Proteins In Coronavirus Replicationsupporting
confidence: 64%
“…A number of studies have addressed possible roles of cellular proteins in coronavirus (mainly MHV) RNA synthesis. In these studies, several members of the hnRNP family (PTB or hnRNP A1, SYNCRIP) were identified based on their ability to bind to viral RNA fragments containing TRS (TRS-L as well as TRS-B) in vitro and, in some cases, to affect MHV replication (Choi et al, 2004;Furuya and Lai, 1993;Li et al, 1997;Zhang and Lai, 1995). Deletion analysis and site-directed mutagenesis of the binding regions of PTB or hnRNP A1 further demonstrated significant inhibition of RNA transcription (Li et al, 1999).…”
Section: Possible Roles Of Cellular Proteins In Coronavirus Replicationmentioning
confidence: 99%
“…These studies were carried out using cytoplasmic extracts generated from poliovirus-infected HeLa cells at 6 h postinfection. Competitor RNAs corresponding to nonradiolabeled 5Ј(Ϫ) RNA probe (lanes 4 to 6), nonradiolabeled 3Ј(Ϫ) RNA probe (lanes 7 and 8), tRNA (lanes 9 and 10), or nonradiolabeled transcript of 20 uridine residues (lanes 11 and 12) were added to reaction mixtures at the indicated molar excess compared to the amount of suggested that while the 5Ј and 3Ј poliovirus negative-strand termini bind to some of the same proteins in the infected cell, they may not necessarily bind all of the same proteins or with the same affinity (17,32). To rule out the possibility that the proteins interacting with the 5Ј(Ϫ) end were binding to the poly(U) sequence at the 5Ј terminus of the probe and not the unique poliovirus RNA nucleotide sequence, we carried out UV cross-linking competition assays using T7 RNA polymerase transcripts consisting of 20 uridine residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other nuclear proteins, including the p100 transcriptional coactivator, PABP, and certain members of the hnRNPs such as hnRNP Q, showed preferential binding to the 3′ end of the coronavirus genome and a positive effect on coronavirus RNA synthesis (95, 97). The contribution of these proteins to host cell interactions in TGEV infection is supported by the formation of a complex including glyceraldehyde 3-phosphate dehydrogenase (GAPDH), glutamyl-prolyl-tRNA synthetase (EPRS), hnRNP Q, and the ribosomal protein L13a, which regulates the expression of inflammatory genes (98, 99).…”
Section: Relevance Of the Cell Nucleus In Coronavirus Rna Synthesismentioning
confidence: 99%